NOS teacher identity: A case study of secondary education novice science teachers. - Luque-Jiménez, Jorge; García-Ruiz, Cristina (My University, 2024)
The understanding of the Nature of Science (NOS) is crucial in developing scientific literacy, a fundamental goal of science education. Scientific literacy extends beyond mere knowledge; it encompasses an understanding of science's methodologies, cultural and social influences, and the evolving nature of scientific knowledge. In this context, the professional identity of teachers, who not only grasp NOS concepts but can also effectively impart this understanding, becomes critical. This study explores the interplay between science teacher identity and their understanding of NOS, emphasizing the importance of targeted NOS instruction in teacher education programs. We conducted a qualitative case study with five novice teachers, each with less than five years of professional experience, using a questionnaire based on NSTA recommendations related to NOS. Employing Atlas.ti software (v 23.3.0) for analysis, we identified 26 codes related to aspects such as the reliability and changeability of scientific knowledge (e.g., theory revision and adaptation, predictive nature of theories) and the naturalistic methods and explanations in science (e.g., explanation of natural phenomena, interrelation of facts, laws, and theories). The results reveal a robust foundation in key NOS aspects, particularly in recognizing the empirical nature of science and its human dimensions. However, a lesser emphasis on the adaptability and revisability of scientific knowledge was observed. This suggests a need for deeper engagement with the concept of the dynamic nature of scientific understanding. Enhancing the novice teachers' grasp of areas such as the evolving nature of scientific knowledge and critical analysis will further solidify their NOS teacher identity, equipping them to deliver a more comprehensive and nuanced science education.
Keywords: Profesores de ciencias - Formación profesional; Ciencia - Estudio y enseñanza secundaria; NOS identity; Teacher identity; Scientific literacy; Qualitative analysis